Nephrolithiasis in related kidney donors - D. V. Perlin; I. N. Dymkov; A. V. Terentyev; A. D. Perlina; I. V. Alexandrov (Трансплантология (Москва), 2023)
Introduction. Long-term results of renal transplantation from living donors are much better than the results of cadaveric transplantations. Recently, because of the shortage of living donors, some centers have started using kidneys from living donors with asymptomatic stones as a potential solution for the problem. However, the optimal surgical solution for such situations has not yet been developed.Aim. To evaluate our obtained transplantation results of using the kidneys from living donors with nephrolithiasis and compare them with the literature data.Material and methods. In the period from 2012-2021, renal transplantations in our clinic were done in three patients from related donors with stones in the kidney. One donor underwent mini-percutaneous lithotripsy one month prior to nephrectomy. The other two underwent simultaneous retrograde lithotripsy and laparoscopic donor nephrectomy. In these cases a holmium or thulium laser was used for the destruction of calculi. All donors underwent laparoscopic retroperitoneal nephrectomy.Results. All stones were successfully removed. There were no surgical complications in donors during and after procedures. Warm ischemia time did not exceed 3.5 minutes. The general length of hospital stay was 10 days in case of predonation stone removal surgery and 6 and 4 days in the cases of simultaneous procedures, respectively. All grafts were transplanted to related recipients. One of the recipients was treated with hemodialysis before transplantation, the other one with peritoneal dialysis. The third recipient underwent preemptive transplantation (before the start of dialysis). The graft function in all cases was immediate. During the follow-up period (9-57 months), no signs of nephrolithiasis were seen in either donors, or recipients.Conclusions. Consideration of potential donors with stones in one kidney might increase the number of living donor renal transplantation. Simultaneous RIRS and laparoscopic donor nephrectomy can be considered as an alternative to sequential operations or ex vivo stone extraction. The presented technique is reproducible, safe and was not associated with an increased length of hospital stay.